Introgression and the fate of domesticated genes in a wild mammal population. Issue 16 (20th June 2013) - Feulner, Philine G. D.; Gratten, Jacob; Kijas, James W.; Visscher, Peter M.; Pemberton, Josephine M.; Slate, Jon.
Abstract When domesticated species are not reproductively isolated from their wild relatives, the opportunity arises for artificially selected variants to be re‐introduced into the wild. However, the evolutionary consequences of introgression of domesticated genes back into the wild are poorly understood. By combining high‐throughput genotyping with 25 years of long‐term ecological field data, we describe the occurrence and consequences of admixture between a primitive sheep breed, the free‐living Soay sheep of St Kilda, and more modern breeds. Utilizing data from a 50 K ovine SNP chip, together with forward simulations of demographic scenarios, we show that admixture occurred between Soay sheep and a more modern breed, consistent with historical accounts, approximately 150 years ago. Haplotype‐sharing analyses with other breeds revealed that polymorphisms in coat colour and pattern in Soay sheep arose as a result of introgression of genetic variants favoured by artificial selection. Because the haplotypes carrying the causative mutations are known to be under natural selection in free‐living Soay sheep, the admixture event created an opportunity to observe the outcome of a 'natural laboratory' experiment where ancestral and domesticated genes competed with each other. The haplotype carrying the domesticated light coat colour allele was favoured by natural selection, while the haplotype associated with the domesticated self coat pattern allele was associated with decreased survival. Therefore, we demonstrate that introgression of domesticated alleles into wild populations can provide a novel source of variation capable of generating rapid evolutionary changes.